Paradox and privilege: A 55-year follow-up of the mortality of Yale College graduates - Stephen J. Kunitz; Daniel Horowitz (Elsevier, 2016)
Objective: Two hypotheses were tested: 1. People from privileged backgrounds had better survival than those from less privileged backgrounds. 2. The advantages of privilege were vitiated by fraternity membership. Methods: A 55-year retrospective cohort study of survival since 1960 of 945 graduates of Yale College followed to 2015. Results: The survival of graduates of private secondary schools (the privileged group) did not differ from that of public school graduates. However, graduates of private secondary schools who had not joined a fraternity in college had significantly better survival than private school graduates who had joined fraternities and than public school graduates, whether fraternity members or not. Conclusions: The benefits of a privileged background in respect of survival were undermined by fraternity membership. It is suggested that both self-selection and substance mis-use may have contributed to the survival difference. Keywords: Survival, Mortality, Social status, Fraternities, Alcohol, Social capital